Guidelines for Developing Ethical Leadership of Administrators according to the Perception of Teachers in School Under Secondary Educational Service Area Office Khon Kaen - Srikaewtum, Montree (Journal of Graduate MCU KhonKaen Campus, 2025)
The objectives of this research were to 1) study ethical leadership of school administrators according to the perception of teachers and 2) to recommend guidelines for developing ethical leadership of school administrators according to the perception of teachers under Khon kaen Secondary Education Service Area. This research was a descriptiv research. The sample group consisted of 354 teachers under Khon kaen Secondary Education Service Area using stratified random sampling method. The research instruments were a 5-level rating scale questionnaire with content validity of 0.67-1 and questionnaire reliability of 0.97, and a semi-structured interview. The statistics used analyze data comprised frequency, percentage, mean, standard deviation, median, and interquartile range. The study results were found that: 1. The ethical leadership of school administrators according to the perception of teachers, in overall, was found to be at the highest level. 2. The guidelines for developing ethical leadership of school administrators according to the perception of teachers consisted of 4 components: 1) In aspect of honesty, school administrators should administer schools according to the rule of law with full commitment and determination and there should be a meeting to clarify the details every time before implementing it and not distorting the facts. 2) In aspect of justice, school administrators should administer the schools systematically with neutrality and be kalyanamitta, there should be a transparent work network creation, not taking an advantage of subordinates, and there the duties according to the correct process should be performed. 3) In aspect of respect for equality, school administrators should create a network for exchanging knowledge among school administrators to share experiences and good practices in promoting equality. 4) In aspect of caring for others, school administrators should focus on giving encouragement, building confidence, and taking care of subordinates, especially when subordinates were facing problems or were sick, in order to build morale and encouragement in working.